2010
DOI: 10.1093/tropej/fmq115
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Diagnosis Disclosure and its Correlates in HIV-Infected North Indian Children

Abstract: This facility-based cross-sectional study was conducted to determine the patterns of disclosure of HIV positive serostatus among 145 Indian children aged >5 years. Only 60 (41.4%) children were aware of their HIV-positive status. Disclosure was most frequently done by parents [51/60 (85%)] at a mean age of 9.1 ± 1.4 years. The rate of inaccurate disclosure was high [64/85 (75.3%)]. No information regarding their illness was given to 21/85 (24.7%) children. The most common reason for non-disclosure was that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 19 publications
10
77
1
3
Order By: Relevance
“…When full disclosure occurs, children are told the name of the illness (HIV and/or AIDS), disease specific information, and how they acquired the disease. The rates of disclosure ranged from a low of 17 to 70% as reported in several studies, 4,8,17,18,19,20,21,22,23,24 non-disclosure 23% and deception 20% particularly in young children. 17 Partial disclosure was reported to vary between 35-40% by Gortmarker et al, 4 and Weiner et al 9 Partial disclosure often occurs in conjunction with illness deception.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…When full disclosure occurs, children are told the name of the illness (HIV and/or AIDS), disease specific information, and how they acquired the disease. The rates of disclosure ranged from a low of 17 to 70% as reported in several studies, 4,8,17,18,19,20,21,22,23,24 non-disclosure 23% and deception 20% particularly in young children. 17 Partial disclosure was reported to vary between 35-40% by Gortmarker et al, 4 and Weiner et al 9 Partial disclosure often occurs in conjunction with illness deception.…”
Section: Introductionmentioning
confidence: 80%
“…4 There is controversy about the age of disclosure with some people advocating for disclosure as early as 5-7 years. 8,23 Age has been reported to be the most important predictor of whether or not the child is disclosed to. 8,9 Methodology Study setting: The study was conducted at Jinja Regional Referral Hospital Paediatric HIV clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Having to watch what is said to the child when disclosure hasn't happened High patient volume Child knows, provider knows child knows, caregiver refuses to disclose Inability to disclose without caregiver's consent Inability to reach certain caregivers Father as head of household blocking disclosure Orphaned children Negative or inaccurate public health messages HIV fears and stigma previously found to be associated with disclosure, 39,40 and caregivers of HIV positive children in the Democratic Republic of Congo reported that having a child attend school made them think more seriously about disclosing. 41 In our study, providers identified attending boarding school as an important symbol of the child's transition to being able to take medications independently and accept management of their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted on PHIV+ diagnosis disclosure in Ethiopia considered children below the age of 15 years or were conducted using a small sample size 14 23–25. In our study, all children had started ART, which was reported as one of the factors associated with disclosure 17. Therefore, we aimed to assess the proportion of PHIV+ diagnosis disclosure and its correlates among caregivers who had PHIV+ children between the ages of 6 and 18 years.…”
Section: Introductionmentioning
confidence: 99%